Practicing the Passion of Pentecost: Re-envisioning Pentecostal Eschatology through the Anatheistic Sacramentality of Richard Kearney - Rice, Monte Lee ca. 20./21. Jh. (Pneuma, 2021)
Abstract Scholars are steadily situating pentecostal studies within the embodiment turn, recognizing its foci as imperative to ongoing twenty-first-century pentecostal/charismatic studies. Yet this enjoins greater movement beyond the earlier “linguistic turn,” which too often overlooked the crucial perspectival role of human flesh. For from the horizons of incarnation and Pentecost, Christian faith propagates God’s turn toward flesh. This suggest that pentecostal spirituality generates an eschatological urgency. Fostering this “urgency” into the twenty-first century, however, requires recasting its source and expression within pentecostal spirituality. Drawing from Acts 2:17 (“I will pour out my Spirit on all flesh”), this essay explores how this turn to the flesh might aptly ground and generate eschatological fervor. Doing so, however, exposes deficiencies with pentecostal sacramentality, recognizing links between it and eschatology. The essay addresses this by engaging Kearney’s “anatheistic sacramentality.” It concludes with several implications with particular attention to the violent tragedy of world hunger.